Ocular Delivery System for Propranolol Hydrochloride Based on Nanostructured Lipid Carrier - Behzad Sharif Makhmal Zadeh; Hassan Niro; Fakher Rahim; Golbarg Esfahani (MDPI AG, 2018)
One drawback of traditional forms of medical ocular dosage is drug dilution by tear; moreover, drugs are rapidly drained away from pre-corneal cavity by tear flow and lacrimo-nasal drainage. Prolonging contact time with different strategies and mucoadhesive vehicles will help to continuously deliver drugs to the eyes. For this study, we prepared and evaluated the effects of a nanostructure lipid carrier (NLC) on propranolol hydrochloride as a hydrophilic drug model for rabbit corneal permeation. Propranolol hydrochloride NLC was prepared using cold homogenization. The lipid was melted, then the drug and surfactant were dispersed and stirred into the melted lipid. This fused lipid phase was scattered in aqueous solution containing the cosurfactant at 4 °C and then homogenized. We evaluated particle size, drug loading, drug release, and NLC permeability through rabbit cornea as well as the formula’s effect on the cornea. Our results show that drug loading efficiency depended on the surfactant/lipid ratio (S/L) and the percentages of liquid lipid and Transcutol (Gattefosse, Saint-Priest, France) (as solubilizer). Drug release data were evaluated with the Higuchi model and a significant correlation was shown between the S/L ratio and the amount of drug released after 4 and 48 h. NLC formulations improved propranolol hydrochloride permeation. We conclude that the effect of the NLC formulations was due to mucoadhesive and film forming properties.